Media Framing of Kaesang Pangerep’s PSI Chairmanship by Tribunnews.com - Irawan, Rahmat Edi; Tripalupi, Merry Fridha (Journalism Study Program, Faculty of Communication Sciences, Universitas Padjadjaran, 2024)
Media undeniably has a great influence in the political sphere today. The interdependence between media and politics is an interesting discussion because it should be an institution that disseminates information neutrally, no tendency to certain groups. However, today’s media in Indonesia exacerbates the phenomenon of political mediatization. This study aims to provide new insights into how Tribunnews.com uses framing to shape political narratives in the context of news coverage of Kaesang Pangarep’s rise to the leadership of PSI party. This study combines qualitative methodology with the framing analysis method based on the theories of Gerald Kosicki and Zhongdang Pan. It examined the Tribunnews.com report, edition September 30th 2023 titled “Observer Suspects Megawati’s Anger over Kaesang Joining PSI”. Tribunnews.com was chosen because the news was only reviewed from the observer’s side. Hence, this research attempted to reveal how Kaesanng’s rise to the leadership of the PSI party was framed by Tribunnews.com. The results of the research based on the Zhongdang Pan and Kosicki model demonstrated that Tribunnews.com constructed Megawati’s alleged anger, yet the news was not followed with reliable sources for balanced reporting. Tribunnews.com also mediatized the use of bombastic titles and content to increase news appeal. This requires a public concern because the media, which should act as the fourth pillar of democracy, instead tend to mediatize the news only for attaining public attention.